Observations of B0s → ψ(2S)η and B0(s) → ψ(2S)π+π− decays - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; Grünberg, Oliver; et al. (Nuclear physics. B, Particle physics, 2013)
First observations of the Bs0→ψ(2S)η, B0→ψ(2S)π+π− and Bs0→ψ(2S)π+π− decays are made using a dataset corresponding to an integrated luminosity of 1.0 fb−1 collected by the LHCb experiment in proton-proton collisions at a centre-of-mass energy of s=7 TeV. The ratios of the branching fractions of each of the ψ(2S) modes with respect to the corresponding J/ψ decays areB(Bs0→ψ(2S)η)B(Bs0→J/ψη)=0.83±0.14(stat)±0.12(syst)±0.02(B),B(B0→ψ(2S)π+π−)B(B0→J/ψπ+π−)=0.56±0.07(stat)±0.05(syst)±0.01(B),B(Bs0→ψ(2S)π+π−)B(Bs0→J/ψπ+π−)=0.34±0.04(stat)±0.03(syst)±0.01(B), where the third uncertainty corresponds to the uncertainties of the dilepton branching fractions of the J/ψ and ψ(2S) meson decays.
Im Titel sind "0", "+" und "-" hochgestellt und "s" und "(s)" tiefgestellt
LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, B. Leverington, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 586
Gesehen am 24.03.2021